Pertanggungjawaban Pidana Korporasi dalam Tindak Pidana Kebakaran Hutan dan Lahan - Reza Fadhli (Universitas Islam Indonesia, 2018)
This legal research aims to first, identify the criteria to determine if a corporation causes land and forest fires, and second, how would the corporate criminal liability answer for the crime in clearing the lands burning them aw well as the violation of the environmental quality standards due to the land and forest fires in accordance with Law No. 32 of 2009 on Environmental Protection and Management. This is a normative legal research, the use of legal materials includes primary and secondary legal materials through the collection of data from literature study. The method used to analyze the data is qualitative analysis. The reseach concluder fisrt, criteria for corporations committing criminal acts on land and forest fires is if the crime is committed by, for or on behalf of a business entity carried out by a person in a work relationship or other relationship within the scope of work of a business entity. Second, the form of corporate criminal liability in criminal acts on land and forest fires is criminal liability identification. Because there are errors in the corporation management (director) as the person in charge of the business whose business has the possibility/great impact on environmental damage and pollution such as land and forest fires fires and violating the environmental quality standards.